Structural investigation and optical properties of cobalt aluminate pigments derived from thermal decomposition of mixed-metal nitrate co-crystals - Yaemphutchong S. (2023)
In this study, the coloration mechanism of cobalt aluminate spinel materials derived by thermal decomposition of the co-crystallized mixed-metal precursors has been reported. The structural alteration of cobalt aluminates, along with the origins of chroma values at the different calcination temperatures from 600 °C to 1200 °C were thoroughly investigated by combining XRF, XRD, XAS, UV-VIS DRS, FT-IR, and FT-Raman techniques. In-depth analyses of structural information and corresponding optical properties suggested that the coloration can be modified by controlling Co2+/Co3+ contents and their site occupancies in the spinel structure by adjusting calcination temperatures and selecting the counter ions with appropriate oxidizing power. The interplays among (1) the oxidation process at low temperatures, (2) the deoxidation process at high temperatures, (3) the reduction in the degree of spinel inversion (toward the emerging of normal-spinel CoAl2O4 structure), and (4) the existence of the minor Al2O3 domains are found to be key imperatives for tailoring the color appearances of cobalt aluminate powders in the broad range from black, dark-green, green, greenish-blue, dark-blue, towards bright-blue. Herein, we reveal the correlation between the synthetic parameters and the structural features of the obtained spinel-based materials, which could further exhibit the crucial procedure to control the coloration of inorganic pigments systematically.